Additional value of CMR feature tracking parameters for the evaluation of the risk of complex ventricular arrhythmias and sudden cardiac death in patients with Mitral Valve Prolapse. (4th February 2022) - Pavon, A; Guglielmo, M; Arangalage, D; Bonanni, M; Angelini, G; Paiocchi, V; Leo, L; Valgimigli, M; Pedrazzini, G; Pontone, G; Monney, P; Faletra, F
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Mitral valve prolapse (MVP) with mitro-annular disjunction (MAD) has been associated with complex ventricular arrhythmias (c-VA) and sudden cardiac death (SCD) but risk stratification in this subset of patients remains insufficiently characterized. The aim of this study was to investigate the association between deformation parameters assessed by feature tracking (FT) cardiac magnetic resonance (CMR) in patients with MVP and MAD (MVP-MAD) and c-VA and/or SCD. Methods: We included 23 patients (47 ± 13 years; 43 % males) with MVP-MAD, of whom 17 (74 %) presented with c-VA and 6 (26%) with SCD, as well as 20 age- and sex-matched controls (50 ± 18 years; 57% males). All patients underwent CMR with assessment of MAD length, late gadolinium enhancement (LGE), extracellular volume (ECV), global and regional longitudinal (LS), and circumferential strain (CS). RATIO-CS was defined as the ratio between regional CS in the basal inferolateral and mid-inferolateral walls (fig.1). Results: In MVP-MAD patients, non-ischemic LGE of the LV inferior and inferolateral wall was observed in 21 patients (50%). As compared to controls, MVP-MAD patients showed lower global LS (-18.7 ±4.1 vs -24.7 ± 5.7 p < 0.001), higher native T1 relaxation time and ECV of the left ventricle (LV) inferolateral wall (1104 ± 63ms vs 1083 ± 66ms p < 0.029 and 0.31 ± 0.03 vs 0.27 ± 0.04 p 0.003), lower CS and LS of the LV mid and inferolateral segments (p < 0.005). Logistic univariate regression analysis showed an increased risk of c-VA in case of LGE presence (OR: 9.52 [2.28-39.7] p = 0.002), a high number of LV segments with LGE (OR: 1.78 [1.21-2.63] p = 0.004), GLS (OR: 1.58 [1.21-2.07] p < 0.001), decreased inferolateral mid ventricular wall CS (OR: 1.41 [1.16-1.72] p < 0.001), decreased basal and mid-ventricular inferolateral wall LS (OR: 1.11 [1.00-1.23] p = 0.047 and OR: 1.62 [1.22-2.13] p < 0.001 respectively), increased native T1 times (OR: 1.01 [1.00-1.02] p = 0.039), increased ECV of the basal infero-lateral wall  (OR: 4.93e + 07 [1.22-1.98e + 15] p = 0.047) and decreased RATIO-CS (OR: 7.48 [1.87-30.00] p = 0.005) (table 1). In multivariate analysis the presence of a lower LS in the basal inferolateral wall remained an independent predictor of c-VA (OR: 1.62 [1.22-2.13.00] p = 0.0007) and RATIO-CS remained an independent predictor of SCD (OR: 7.73 [1.78-33.60] p = 0.006). Conclusion: Lower inferolateral LS and RATIO CS are respectively associated with c-VA and SCD in MVP-MAD patients.  FT may provide additional value for risk stratification on top of standard CMR parameters in this subset of patients.